2018
DOI: 10.1016/j.npbr.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The association between norepinephrine and metabolism in patients with major depression

Abstract: Background: Previous studies indicate that levels of plasma norepinephrine (p-NE) are altered in depressed patients. However, it is unclear whether altered NE metabolism is involved in the pathogenic association between depression and cardiovascular disease. The aim of the present study was, firstly, to investigate if p-NE levels differ between patients with major depression and healthy controls. Secondly, the study sought to assess the associations between p-NE and metabolic variables in all participants. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The study reported that sorrow or sad feelings arise in specific cerebrum when the norepinephrine level is too low (Delgado & Bogousslavsky, 2018). Variations in the norepinephrine levels do not influence the mindset of each individual (Futtrup et al., 2018). Further, drugs explicitly focusing on norepinephrine might mitigate suffering in certain individuals, yet not in others (Moret & Briley, 2011).…”
Section: Role Of Neurotransmitters In Depressionmentioning
confidence: 99%
“…The study reported that sorrow or sad feelings arise in specific cerebrum when the norepinephrine level is too low (Delgado & Bogousslavsky, 2018). Variations in the norepinephrine levels do not influence the mindset of each individual (Futtrup et al., 2018). Further, drugs explicitly focusing on norepinephrine might mitigate suffering in certain individuals, yet not in others (Moret & Briley, 2011).…”
Section: Role Of Neurotransmitters In Depressionmentioning
confidence: 99%